Association between Functional Movement Screen Scores and Athletic Performance in Adolescents: A Systematic Review - Katie Fitton Davies; Ryan S. Sacko; Mark A. Lyons; Michael J. Duncan (MDPI AG, 2022)
This study systematically reviews the literature examining the relationship between Fundamental Movement Screen (FMS©) scores and athletic performance in youth. We searched English-language papers on PubMed/MEDLINE, SportsDiscus, CINAHL, and EBSCO for the following inclusion criteria: Participants aged between 11 and 17 years, studies had to include the Functional Movement Screen© (FMS©) and at least one of the following performance outcomes, highlighted by athletic development models (i.e., long-term athletic development (LTAD), youth physical development (YPD)): agility, speed, power, strength, endurance, and balance (YPD), fitness (LTAD), or sport-specific skill (LTAD and YPD). A total of 3146 titles were identified, with 13 relevant studies satisfying the inclusion criteria after full-text screening. The results of this systematic review suggest that children and youth who score highly on the FMS© also tend to have better scores for agility, running speed, strength, and cardiovascular endurance. The strength of associations was weak to moderate in nature. Only one study was considered or controlled for biological maturation in their analysis. These results provide evidence that, while there is a relationship between FMS© scores and tests of athletic performance in youth, they are not the same thing and should be considered conceptually different constructs.